Sigmoid Venous Thrombosis in JAK2 V617F Mutated Polycythemia Vera - Martins De Oliveira Filho, Cilomar; Gavralidis, Alexander (Case Reports in Hematology, 2022)
A 60-year-old female presented with headaches, blurry vision, diplopia, and dizziness for six weeks. Her workup revealed an elevated hematocrit, thrombocytosis, high ferritin, and normal erythropoietin. She was diagnosed with polycythemia vera with the JAK2 V617F mutation. The patient underwent magnetic resonance venography, which showed left-sided sigmoid venous thrombosis. She was placed on low-molecular-weight heparin, with a plan to transition to oral anticoagulation after four weeks and repeat imaging in three months to assess for resolution. Thrombotic events may occur in patients with polycythemia vera, and a JAK2 mutation further heightens that risk. Even so, intracranial venous thrombosis is not among the most common events, and it should be kept in the differential for any patient with myeloproliferative neoplasms presenting with new neurological symptoms.